Resveratrol interrupts the pro-invasive communication between cancer associated fibroblasts and cholangiocarcinoma cells. (28th August 2018) - Thongchot, Suyanee; Ferraresi, Alessandra; Vidoni, Chiara; Loilome, Watcharin; Yongvanit, Puangrat; Namwat, Nisana; Isidoro, Ciro
Abstract: Cholangiocarcinoma (CCA), the cancer arising from the epithelial cells of bile ducts, is a prototype of inflammatory-driven cancer. Cytokines released by cancer associated fibroblasts (CAFs) play a pivotal role in CCA progression, driving the epigenetic Epithelial-to-Mesenchymal transition and the growth and metastasization of CCA cells. Consistently, the conditioned medium from CCA-derived CAFs further stimulated the secretion of IL-6, and to a lesser extent of IL-8, by CCA cells. CCA has a poor prognosis, because of late diagnosis and of high resistance to radio- and chemo-therapy of CCA cells. Targeting the CAFs and their secretion could be an alternative option. We found that while IL-6 indeed promoted the cell migration of invasive CCA cells, the nutraceutical Resveratrol strongly counteracted this effect both in CCA cells and in immortalized cholangiocytes. More importantly, here we show that Resveratrol has the potential to abrogate the secretion of IL-6 by CAFs. While the conditioned medium from CAFs strongly induced IL-6 mediated motility of CCA cells, the conditioned medium from CAFs pre-treated with Resveratrol completely halted cancer cell motility and reverted the N-to E-cadherin switch in migrating cells. This effect was associated with stimulation of autophagy in the cancer cells. This is the first demonstration that CAFs secretory products directly affect the regulation of autophagy and consequently the behavior of CCA cells, and that a nutraceutical may revert the malignant phenotype of cancer cells by acting on CAFs metabolism and secretion. Highlights: CAFs secretion inhibits autophagy in cholangiocarcinoma cells. CAFs secretion stimulates migration of cholangiocarcinoma cells. Resveratrol abolishes the secretion of pro-migratory cytokines from CAFs. Secretion from Resveratrol-treated CAFs loses the inhibitory effect on cholangiocarcinoma autophagy.